Black chronicle s a segment of the media agenda in daily newspapers in Serbia - Jevtović, Ana Z.; Bajić, Predrag Đ.; Vojinović, Maja M. (Sociološki pregled, 2022)
The paper problematizes substantial presence of black chronicle in print media reporting. Through a quantitative and qualitative analysis of the content of ten daily newspapers in Serbia, we researched genre characteristics and editorial policies used in presenting the content from the black chronicle segment. It can be seen that daily newspapers on a large-scale deal with the topic of violence and death, but also that the reporting quality does not correspond to the quantity of the published texts. Looking at the content, it can be concluded that serious daily press invests certain efforts in the maintenance of professional standards of the journalist profession, unlike tabloids that dominate the media space. During the analyzed time interval, there was almost not a single day when tabloids, on the pages reserved for the content from the black chronicle segment, did not reveal some details related to the lives of victims, possible perpetrators of criminal acts, as well as other actors, along with the observed violations of the rules of journalist ethics. Therefore, it is necessary to work on emancipation in two directions, towards greater responsibility of editorial staff, editors and journalists, and towards stronger media literacy of the public itself.
Keywords: press; media agenda; black chronicle; tabloidization; sensationalism